Four new species of Hemicaecilius Enderlein (Lachesillidae: Psocoptera) from Valle del Cauca, Colombia - Aldrete, Alfonso N. García; Obando, Ranulfo González; Carrejo, Nancy S. (Zootaxa, 2012)
Four related species of Hemicaecilius, from Valle del Cauca, Colombia, are here described and illustrated. They constitutea species assemblage distinct from two of the known species of the genus, H. venezolanus and H. cuzcoensis, found to thenorth and south, respectively from Valle del Cauca, along the Andes. The types are deposited in the Entomological Museum, Universidad del Valle, Santiago de Cali, Colombia (MUSENUV).